Overview of Pathogenesis and Key Clinical Features of Hypercortisolism - Said, Nassim; Nikolashvili, Mariam (Caucasus Journal of Health Sciences and Public Health, 2020)
Cushing’s syndrome, a rarely occurring condition due to over secretion of glucocorticoids; namely, cortisol.Cortisol is acatabolic hormone, originated from the Zona fasciculata in the adrenal cortexunder the control of Hypothalamus-pituitary axis as a response to various stimuli.Pituitary gland after receiving a releasing signal from hypothalamus (by CRH=Corticotropin releasing hormone) secretes a hormone – ACTH, which gets delivered to the adrenal cortex via blood to initiate cortisol production. Hypercortisolism can occur due to several abnormalities:1)hypersecretion of ACTH hormone usually associated with anterior pituitary tumors, 2)ACTH secreting cells which overproduce this hormone could be also located ectopically, for example in the lung tissue in some rare type of cancers, such assmall cell lung cancer.3)Furthermore, hypercortisolism can be caused by adrenal gland tumors, 4) it can be drug-induced (or exogenous) as a result of oral intake of steroids which eventually leads to adrenal hypoplasia. It should be mentioned that chronical alcoholic patients can develop Cushing’s syndrome symptoms and they might even haveblood cortisol levels similar as seen in Cushing’s syndrome patients, in this case it is referred as pseudo-Cushing’s syndrome. Determining the etiology of the Cushing’s syndrome is a bit challenging for the clinicians since there are several pathologic cases that lead to hypercortisolism; salivary cortisol measurement, dexamethasone suppression test, 24-hour urinary free cortisol test, adrenal CT, and pituitary MRI are usually used for analysis. Patients with Cushing’s in most instances have very distinctive features: such as a moon face, hypertension, poor wound healing, skin bruising, striae (reddish stretch marks), dark facial hair (hirsutism), android type of obesity, facial acneand amenorrhea in women; this is all due to elevated blood cortisol, in consideration of having the Zona reticularis neighboring the Zona fasciculata in adrenal gland tumors elevated sex hormones (androgens) is also seen which is responsible for some of the clinical features that are mentioned earlier. Cushing’s syndrome is most likely to be seen in adults between 30 to 50 years, and women areat a higher risk for developing this disorder.